If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(c + 10) + 3(2c + -6) = 0 Reorder the terms: -1(10 + c) + 3(2c + -6) = 0 (10 * -1 + c * -1) + 3(2c + -6) = 0 (-10 + -1c) + 3(2c + -6) = 0 Reorder the terms: -10 + -1c + 3(-6 + 2c) = 0 -10 + -1c + (-6 * 3 + 2c * 3) = 0 -10 + -1c + (-18 + 6c) = 0 Reorder the terms: -10 + -18 + -1c + 6c = 0 Combine like terms: -10 + -18 = -28 -28 + -1c + 6c = 0 Combine like terms: -1c + 6c = 5c -28 + 5c = 0 Solving -28 + 5c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '28' to each side of the equation. -28 + 28 + 5c = 0 + 28 Combine like terms: -28 + 28 = 0 0 + 5c = 0 + 28 5c = 0 + 28 Combine like terms: 0 + 28 = 28 5c = 28 Divide each side by '5'. c = 5.6 Simplifying c = 5.6
| -132=39 | | -3v-v=16 | | -9b=-117 | | 35x+9=55 | | -n+2n=4 | | -8b=-117 | | -7x-3=4 | | 6n-7=2n+17 | | 11x-4x^2-344= | | 1/3(s-2)=s+4 | | (x+9)(x+9)=18 | | 344=11x-4x^2 | | 3(2z-1)=6z+5 | | -28=-7(1-8b)-5(4b-3) | | (x-2)(x+3)=24 | | 32x+1=3+6 | | 2x+1+6x=81 | | -6n+9=1-8n | | -17b=-2.21 | | -17=-2.21 | | 7x-3=2x-12 | | y=-4+3x | | -34e=-3.74 | | 5x+1-7=-1 | | 25+37-2x=11 | | y=-3x+(-4) | | 8y+8=21 | | 5(9p+6)=8p | | 4x^2-6x=3 | | y=abs(x) | | 3x+2(x+2)=13-(x+2) | | -42-21= |